The grapevine of the black South : the Scott Newspaper Syndicate in the generation before the civil rights movement - Aiello, Thomas, 1977- (Print culture in the South., 2018)
"The Scott Newspaper Syndicate, run by the owners of the Atlanta Daily World, included more than 240 black newspapers between 1931 and 1955. It became after World War I the modern version of the nineteenth century kinship network, the grapevine, and it looked much the same and served similar ends. In a pragmatic effort to avoid racial confrontation developing from white fear, newspaper editors developed a practical radicalism that argued on the fringes of racial hegemony and saving their loudest vitriol for tyranny that wasn't local and thus left no stake in the game for would-be white saboteurs. But the Syndicate did not remain in the South. Its membership followed the path of the Great Migration into the Midwest and West. The comparative reach of the SNS and its hundreds of newspapers was simply unparalleled. This book examines that reach, and in the process reexamines historical thinking about the Depression-era black South, the information flow of the Great Migration, the place of southern newspapers in the historiography of black journalism, and even the ideological and philosophical underpinnings of the civil rights movement"--